2022
DOI: 10.1002/ejoc.202200049
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Functionalization of a Tetraphenylethylene Aromatic Scaffold with Ynamides or Tetracyanobutadienes: Synthesis and Optical Properties

Abstract: Ynamides are useful and versatile building blocks in organic synthesis, from which 1,1,4,4‐tetracyanobutadienes (TCBD) can be prepared for application in molecular electronics. However, their insertion onto multi‐functional molecular scaffold remains a synthetic challenge. In this work, we report the two‐steps synthesis in good isolated yield (64 % overall, 89 % stepwise) of a tetraphenylethylene (TPE) bearing four ynamides, and its further one‐step conversion into the tetra‐TCBD derivative through a [2+2] cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The strong push–pull effects result in electron polarization (also often termed as ground-state charge transfer), resulting in a new low-energy optical transition extending the optical coverage. Making use of the facile reaction and optical properties, they have extensively explored building TCBD-substituted push–pull systems and polymers as promising materials for photovoltaic applications. Our groups have explored a wide variety of donor-functionalized TCBD-based molecular systems exhibiting novel optical and excited-state properties including ultrafast charge transfer and intervalence charge transfer properties. …”
Section: Introductionmentioning
confidence: 99%
“…The strong push–pull effects result in electron polarization (also often termed as ground-state charge transfer), resulting in a new low-energy optical transition extending the optical coverage. Making use of the facile reaction and optical properties, they have extensively explored building TCBD-substituted push–pull systems and polymers as promising materials for photovoltaic applications. Our groups have explored a wide variety of donor-functionalized TCBD-based molecular systems exhibiting novel optical and excited-state properties including ultrafast charge transfer and intervalence charge transfer properties. …”
Section: Introductionmentioning
confidence: 99%
“…The easy synthetic methods also led to the formation of a variety of molecules for a wide range of applications. 45,46 These properties encouraged us to use TCBD for transistor applications. TCBD and TAA are strong electron-accepting and donating units; IQ is considered as a weak acceptor or π-terminal unit.…”
Section: Introductionmentioning
confidence: 99%
“…These chromophores have been widely considered as suitable small molecules for organic electronics, since their orbital energy levels can be easily controlled by judiciously choosing donors and acceptors . However, the synthesized 1,1,4,4-tetracyanobuta-1,3-dienes (TCBDs) have largely been found to be nonemissive/negligible due to radiation-less decay pathways mediated by photoinduced electron transfer/twisted ICT phenomena or charge separation. Despite the fact that emissive TCBD chromophores have been rarely reported, their numerous applications continue to demand their synthesis. Nevertheless, Li and co-workers have observed aggregation-induced emission (AIE) with a quantum yield (Φ F ) of 8.5% in hexane during the morphological transition into vesicle/nanotube nanostructures in the aggregate-friendly designed (TCBD) 2 OPV 3 molecule .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain emissive TCBDs, another approach was made by several groups, i.e., fluorophore conjugation with TCBDs; however, only a few reports have successfully shown luminescence behavior. For example, Trolez and co-workers demonstrated that the ynamide- based TCBD conjugated with fluorophores achieved notable photoluminescence (PL), including an NIR emission in organic apolar solvents, e.g., cyclohexane, with a remarkable quantum yield of 7.6% , and a weak NIR emission in the solid state due to the AIE synthon of tetraphenylethene . Using a similar approach and varying polyaromatics, a significant increase of the luminescence lifetime was demonstrated in the solid state in comparison to that in solution .…”
Section: Introductionmentioning
confidence: 99%